1999
DOI: 10.1073/pnas.96.2.778
|View full text |Cite
|
Sign up to set email alerts
|

A cytochromeb5is required for full activity of flavonoid 3′,5′-hydroxylase, a cytochrome P450 involved in the formation of blue flower colors

Abstract: The substitution pattern of anthocyanin pigments is a main determinant of f lower color. Flavonoid 3,5-hydroxylase (F35H) is a cytochrome P450 enzyme (Cyt P450) that catalyzes the 3,5-hydroxylation of dihydrof lavonols, the precursors of purple anthocyanins. Species such as rose and carnation lack F35H activity and are, therefore, unable to generate purple or blue f lowers. Petunia, on the other hand, contains two loci, termed hf1 and hf2, that encode a Cyt P450 with F35H activity. Here we report the identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(100 citation statements)
references
References 37 publications
2
98
0
Order By: Relevance
“…A possible involvement of Cytb5 in the determination of flower color was also described: de Vetten and collegues (de Vetten et al 1999) reported that the inactivation of the relative gene by transposon mutagenesis resulted in a reduced 3′,5′ substi-tution of anthocyanins. In this work, we describe for the first time, to our knowledge, the discovery of this protein in grape skins.…”
Section: Other Proteinsmentioning
confidence: 99%
“…A possible involvement of Cytb5 in the determination of flower color was also described: de Vetten and collegues (de Vetten et al 1999) reported that the inactivation of the relative gene by transposon mutagenesis resulted in a reduced 3′,5′ substi-tution of anthocyanins. In this work, we describe for the first time, to our knowledge, the discovery of this protein in grape skins.…”
Section: Other Proteinsmentioning
confidence: 99%
“…Previous experiments had shown that an1 Ϫ petals lack transcripts of at least nine structural anthocyanin genes (see, e.g., Quattrocchio et al, 1993;Kroon et al, 1994;de Vetten et al, 1999) and of one potential regulatory gene, Pmyb27, which encodes a protein with similarity to MYB-domain transcription factors (Mur, 1995). Thus, AN1 might induce dfr transcription directly (e.g., as part of the transcription complex on the dfr promoter) or indirectly (by inducing the expression of an intermediate regulator such as MYB27).…”
Section: An1 Is Directly Involved In Transcription Activation Of Dfr mentioning
confidence: 99%
“…P450s are important catalysts in the anthocyanin pathway, one arm of which leads to the formation of blue delphinidin-derived pigments in such owers as petunias (34). The P450s critically involved here catalyze the 3 0 -and 5 0 -hydroxylation of the anthocyanin B ring but require a cytochrome b 5 for full 5 0 hydroxylase activity (33). Moreover, the pigments are localized in vacuoles, the pH of which critically in uences pigment color.…”
Section: Genetic Engineering Of Novel Pigments In Plantsmentioning
confidence: 99%
“…Other applications can also be envisaged, such as the in situ production of pigment in plant tissue, speci cally owers (e.g., ower crops) and bre (e.g., cotton) (33,34). The "Holy Grail" of horticulture is the blue rose; such a novelty as an engineered blue rose could impact signi cantly on the cut-ower market for roses, which is worth over $5 billion per year in the United States alone (35).…”
Section: Genetic Engineering Of Novel Pigments In Plantsmentioning
confidence: 99%